2021
DOI: 10.1007/s15010-021-01737-z
|View full text |Cite
|
Sign up to set email alerts
|

Clinical course and risk factors for severe COVID-19 among Italian patients with cystic fibrosis: a study within the Italian Cystic Fibrosis Society

Abstract: Purpose To describe the clinical course of COVID-19 in patients with cystic fibrosis (CF) and to identify risk factors for severe COVID-19. Methods We conducted a prospective study within the Italian CF Society. CF centers collected baseline and follow-up data of patients with virologically confirmed SARS-CoV-2 infection between March 2020 and June 2021. Odds ratios (ORs) for severe SARS-CoV-2 (as defined by hospital admission) were estimated by logistic regression mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
68
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(73 citation statements)
references
References 32 publications
2
68
0
2
Order By: Relevance
“…However, the course of COVID-19 disease in patients with CF appears to be favorable [ 1 , 2 , 12 ]. Nevertheless, recent studies have shown that lung and pancreatic impairment are risk factors for severe COVID-19 in these patients [ 4 , 12 ]. Therefore, any CF patient with SARS-CoV-2 infection requires a comprehensive evaluation, taking into account all associated comorbidities, in order to tailor a personalized management plan.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the course of COVID-19 disease in patients with CF appears to be favorable [ 1 , 2 , 12 ]. Nevertheless, recent studies have shown that lung and pancreatic impairment are risk factors for severe COVID-19 in these patients [ 4 , 12 ]. Therefore, any CF patient with SARS-CoV-2 infection requires a comprehensive evaluation, taking into account all associated comorbidities, in order to tailor a personalized management plan.…”
Section: Discussionmentioning
confidence: 99%
“…For patients with cystic fibrosis (CF), less information is available in field literature, and some studies point to an overall lower incidence of SARS-CoV-2 infection in this patient population [ 1 , 2 ], but a higher rate of hospitalization among them [ 3 ]. Furthermore, once infection does occur, the patient is considered to be at risk of severe COVID-19 and this risk may be dependent on the underlying degree of lung damage, and also the degree of pancreatic or liver damage [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…A history of transplantation was associated with higher rates of hospitalization (82% versus 53%) and intensive care support (26% versus 5.6%) than those PwCF without transplants [1] . Other studies have shown that PwCF with lower lung function, lower body mass index (BMI), and with comorbidities such as diabetes or liver disease were also more likely to have severe infection [ 2 , 3 ]. The Cystic Fibrosis Registry Global Harmonization Group reported data on 105 children with SARS-CoV-2 infection from 13 countries over a 6-month period [3] .…”
Section: Infection With Sars-cov-2mentioning
confidence: 99%
“…Thirty-seven percent of children were treated with oral antibiotics and 46% received intravenous (IV) antibiotics. Overall, studies showed the majority of PwCF with SARS-CoV-2 infection maintain their lung function and were managed with antibiotics either at home or in the community [1] , [2] , [3] .…”
Section: Infection With Sars-cov-2mentioning
confidence: 99%
“…Though initial reports of COVID-19 in CF patients suggested that the disease may not be as severe as expected, these reports were from developed countries and before the period of delta variant [ 5 ]. A recent large prospective series of Italian cohort of 236 CF patients had 18% hospitalizations and 2.5% mortality, which is significantly higher than the general population of similar age group (median age 25 y) [ 6 ]. Risk factors of severe COVID-19 amongst the cohort were low FEV 1 predicted (< 40%), home oxygen support, underweight, organ transplant, diabetes, and liver disease; while the use of dornase alpha and long-term azithromycin were associated with reduced risk [ 6 ].…”
mentioning
confidence: 99%